The Effect of a Cold Compress on Pain During the First Stage of Childbirth at BPM - Nur Hidayatin; Anita Dwi A; Erika Prawitasari (Universitas Airlangga, 2020)
Introduction: Childbirth is a physiological process that happens as part of a woman's development into becoming a mother. The process can be traumatic for some women because of the pain that they experience. Cold compress therapy is one of the non-pharmacological approaches to reducing pain. The objective of this study is to determine the effect of a cold compress on pain in the first stage of childbirth. Methods: This was an experimental study with a one group pretest-posttest design. The population of this research consisted of women who had given birth, totaling 15 respondents. The samples were chosen using Accidental Sampling. The data was taken through observations and it was analyzed using the Wilcoxon Signed Rank test with a significance level of 0,05. Results: There were changes in pain level with a significance value of ρ = 0,008 with a testing rule ρ < 0,05. This shows that the cold pack affected the level of pain during the first stage of childbirth. Conclusions: A cold compress is effective at reducing the pain felt during childbirth. The items used to make a cold compress are easy to find and a woman can make it herself. A cold compress can be given without causing harmful effects for either the babies or the mothers who are giving birth